MODIFICATIONS OF UREA-FORMALDEHYDE RESIN WITH REACTIVE COMPOUNDS - Negmatov, S.S.; Negmatova, K.S.; Ikramova, M.E.; Zhalilov, Sh.N.; Nazarov, S.I.; Niyozov, E.D.; Shirinov, G.K.; Nazarov, N.I.; Bahromov, B.B.; Rasulova, N.F. (Sanoatda raqamli texnologiyalar, 2023)
The article discusses the modification of urea-formaldehyde resin with a reactive compound - benzyl chloride and carried out IR spectroscopic studies. Optimal conditions for the modification of urea-formaldehyde resin and its use in the production of wood-plastic composite board materials for building purposes have been developed.